Proceedings Of The East Asia Joint Symposium On Fields And Strings 2021 Osaka City University, 22-27 November 2021 - Iso, Satoshi; Itoyama, Hiroshi; Maruyoshi, Kazunobu; Nishinaka, Takahiro; Oota, Takeshi; Sakai, Kazuhiro; Tsuchiya, Asato; Yoshioka, Reiji (World Scientific Publishing Company, 2022)
This volume contains the proceedings of the East Asia Joint Symposium on Fields and Strings 2021, held at the Media Center of Osaka City University on November 22-27, 2021. About 160 physicists from all over East Asia attended physically or joined online this symposium and more than 50 researchers presented their results in the invited lectures, the short talks or the poster session. Quantum field theory and string theory in the context of several exciting developments were discussed, which include frontiers of supersymmetric gauge theory, anomalies and higher form symmetries, and several issues on quantum gravity and black holes.